2022
DOI: 10.1002/jev2.12210
|View full text |Cite
|
Sign up to set email alerts
|

Urinary extracellular vesicles contain mature transcriptome enriched in circular and long noncoding RNAs with functional significance in prostate cancer

Abstract: Long noncoding (lnc)RNAs modulate gene expression alongside presenting unexpected source of neoantigens. Despite their immense interest, their ability to be transferred and control adjacent cells is unknown. Extracellular Vesicles (EVs) offer a protective environment for nucleic acids, with pro and antitumourigenic functions by controlling the immune response. In contrast to extracellular nonvesicular RNA, few studies have addressed the full RNA content within human fluids' EVs and have compared them with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…However, at present it is not yet clear how expression of EV contents correlates with the expression in their cells of origin, that is, correlation or anti‐correlation. A recent study that compared the transcriptome of prostate cancer tissue to paired uEV samples, showed that while the complexity for mRNA between sample types was comparable, a set of mRNAs were significantly enriched in uEV (Almeida et al., 2022 ). Moreover, the same study showed that uEV were enriched in mature cytoplasmic mRNA, which was confirmed also in vitro (Almeida et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at present it is not yet clear how expression of EV contents correlates with the expression in their cells of origin, that is, correlation or anti‐correlation. A recent study that compared the transcriptome of prostate cancer tissue to paired uEV samples, showed that while the complexity for mRNA between sample types was comparable, a set of mRNAs were significantly enriched in uEV (Almeida et al., 2022 ). Moreover, the same study showed that uEV were enriched in mature cytoplasmic mRNA, which was confirmed also in vitro (Almeida et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that compared the transcriptome of prostate cancer tissue to paired uEV samples, showed that while the complexity for mRNA between sample types was comparable, a set of mRNAs were significantly enriched in uEV (Almeida et al., 2022 ). Moreover, the same study showed that uEV were enriched in mature cytoplasmic mRNA, which was confirmed also in vitro (Almeida et al., 2022 ). Hence, the applicability of tissue/single cell signatures for deconvolution are not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…All encapsulating cargos, including protein, nucleic acids and lipids, into various body fluids-derived sEVs can be targets for cancer-specific biomarkers, and their potential application in the noninvasive diagnosis of cancer, screening and monitoring of therapeutic responses is strongly expected. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] Regarding the cargo of PJ-derived sEVs, miRNAs and proteins have been studied to identify candidates diagnostic biomarkers for PDAC Figure 1. [25][26][27][28][29] Nakamura et al identified miR-21 and miR-155 in PJ-derived sEVs as potential diagnostic biomarkers of PDAC.…”
Section: Pj-derived Sevs As a Potential Diagnostic And Screening Tool...mentioning
confidence: 99%
“…Almeida et al extracted urinary EVs of PC patients using centrifugation, which they identified with NTA, EM, WB and RNA analyses. The comparison of total RNA-sequencing of FFPE PC tumor tissue and their paired urinary EV measurements highlighted strong differences in circRNA signals between tumor and EVs and suggests an important role of circRNAs in PC detection and treatment [ 4 ].…”
Section: Pathophysiology In Different Urological and Nephrological Or...mentioning
confidence: 99%